Photos on Facebook : an exploratory study of their role in the social lives and drinking experiences of New Zealand university students : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Wellington, New Zealand - Tonks, Anna Patricia (Massey University, 2012)
Many tertiary students, within New Zealand Aotearoa and other Western countries, regularly engage in binge drinking episodes. These are often subsequently displayed on Facebook in photos. Most of the previous research has not addressed the significant role these photos play within contemporary student drinking cultures. The current thesis aimed to explore how New Zealand university students use photos on Facebook, within their drinking experiences, and how these related to their social relationships and student drinking cultures. A social constructionist framework and key conceptualisations from visual ethnography were employed as the theoretical framework for this study. Nine participants (aged 19; 5 female, 4 male) engaged in individual interviews with a researcher and an internet-enabled laptop. The participants showed the researcher their Facebook photos, and discussed their online practices, drinking and socialising. The interviews were transcribed and a discourse analysis was performed. Three primary discourses were identified. The first discourse, the normal, natural and everyday discourse, reflected the embedded and normalised camera culture and Facebook photo culture within the participants’ socialising and drinking practices. The second, the fun, pleasure and humour discourse, demonstrated the positive, light-hearted environment that the camera, Facebook photos and their subsequent online interactions provided. Participants were able to reconstruct and share their drinking episodes because the photos provided the participants with a visual online drinking story. The viewing and interactions with these photos became a post-night-out ritual that allowed participants to relive and continue the drinking experience after it had ended. The third discourse, acceptability and appropriateness, created a boundary or line that was individually and collectively negotiated and used by the participants to constrain and limit what was shared online. In combination, these discourses allowed the participants to present and participate in a normalised, positive and socially acceptable online student drinking culture. The results add to the growing body of literature around online student drinking cultures, and also extend our knowledge of context collapse, unintended audiences, impression management, identity and friendship. The findings are considered in relation to institutional policy, Facebook privacy, corporate ownership, and health promotion, and directions for future research are suggested.
Keywords: Facebook (Electronic resource); Social aspects; University students; College students; Alcohol use; Drinking; New Zealand; Social media